FREQUENCY OF VAGINAL BIRTH AFTER CAESAREAN SECTION AND ITS FETOMATERNAL OUTCOME - Islam Bano; Naz, Sofia; Sidra Rashid; Yasmin Fatima; Pareesae Humayun; Tabassum Muzaffar (Journal of Ayub Medical College Abbottabad, 2023)
Background: Vaginal birth after caesarean section (VBAC) is associated with reduced blood loss and transfusions, fewer infections, and fewer thromboembolic events as compared to caesarean delivery. The current rate of repeat caesarean after one previous caesarean is above the WHO standard of 15%. We aimed to determine the occurrence of VBAC and to determine the occurrence of feto-maternal outcomes in successful VBAC cases so that trials of VBAC can be given to carefully selected patients in order to reduce the rate of repeat caesarean section. Methods: The Combined Military Hospital (CMH) Rawalpindi’s Obstetrics and Gynaecology department conducted this cross-sectional study from March 20 to September 19, 2021. After obtaining ethical committee approval, data was collected using a non-probability, consecutive sampling technique from 150 patients on a self-developed structured proforma. Patients between the age range of 20-35 years with a history of previous lower segment caesarean section, having gestational age between 37-41 weeks and who presented in spontaneous labour were included in this study. After taking informed consent, all women were given a trial of labour and the outcome of the trial was noted. Women were followed for the feto-maternal outcomes. The gathered information was analysed using SPSS version 25.0. Post-stratification, a p-value of 0.05 or lower on the chi-square test was deemed statistically significant. Results: Following a C-section, 28.67% of patients experienced successful vaginal births. PPH was found in 2.32%, scar dehiscence in 0.0%, low birth weight babies in 16.28%, APGAR score <7 at 1 minute was 23.26% and NICU admission as 9.30% in women undergoing vaginal birth after caesarean section. Conclusion: Appropriate selection of patients for the trial of VBAC can help reduce the higher rate of repeat caesarean section after a previous caesarean section and increase the chances of successful vaginal birth.